ANTI MICRO-BIOLOGICAL ANALYSIS OF ARJUNARISTA - Kr. Verma, Akhilesh; Kumar, Neeraj; Gupta, L. N.; d, Arvind (International Journal of Ayurveda and Pharma Research, 2015)
Arjunarista, an imperative Ayurvedic formulation used for treatment of cardiovascular disorders and prepared by fermenting the decoction of specified plant materials i.e. Arjuna twak (Terminalia arjuna), Draksha phala (Vitis vinifera), Madhuk puspa (Madhuka indica), Dhataki puspa (Woodfordia fruticosa) and Jaggery (Saccharum officinarum). Aim: To assess anti-microbial analysis of Arjunarista. Setting and Design: Arjunarista was prepared as per process of Shandhan kalpana mentioned in manuscripts of Ayurveda with consideration of two variations. These variations were at the level of pot like earthen pot and porcelain pot and addition/deletion of flowers of Dhataki (Woodfordia fruticosa (L.) Kurz). Methods and Materials: Micro-biological analysis was done for total bacterial count, total fungal count and specific pathogens. Total bacterial count, total fungal count was done via plate count agar method and potato dextrose agar respectively. Test for specific pathogens like E. coli, Salmonella sp., Staphylococcus aureus & Pseudomonas aeruginosa was done by Violet red bile agar, Salmonella Agar and Mueller Hinton Agar (for last two bacteria). Results: Total bacterial count (TBC) was absent in all batches except one sample of batch II and batch IV respectively. Total fungal count (TFC) was not present in all batches except one sample of batch I. Specific pathogens count were not present at all in any batches. Conclusion: Arjunarista showed anti micro-biological activity irrespective of variations taken in study.